Etoposide-Bound Magnetic Nanoparticles Designed for Remote Targeting of Cancer Cells Disseminated Within Cerebrospinal Fluid Pathways - Engelhard, Herbert H.; Willis, Alexander J.; Hussain, Syed I.; Papavasiliou, Georgia; Banner, David J.; Kwasnicki, Amanda; Lakka, Sajani S.; Hwang, Sangyeul; Shokuhfar, Tolou; Morris, Sean C.; Liu, Bing (Frontiers in Neurology, 2020)
Magnetic nanoparticles (MNPs) have potential for enhancing drug delivery in selected cancer patients, including those which have cells that have disseminated within cerebrospinal fluid (CSF) pathways. Here, we present data related to the creation and in vitro use of new two-part MNPs consisting of magnetic gold-iron alloy cores which have streptavidin binding sites, and are coated with biotinylated etoposide. Etoposide was chosen due to its previous use in the CSF and ease of biotinylation. Etoposide magnetic nanoparticles (“Etop-MNPs’) were characterized by several different methods, and moved at a distance by surface-walking of MNP clusters, which occurs in response to a rotating permanent magnet. Human cell lines including D283 (medulloblastoma), U138 (glioblastoma), and H2122 (lung adenocarcinoma) were treated with direct application of Etop-MNPs (and control particles), and after remote particle movement. Cell viability was determined by MTT assay and trypan blue exclusion. Results indicated that the biotinylated etoposide was successfully bound to the base MNPs, with the hybrid particle attaining a maximum velocity of 0.13+0.018 cm/sec. Etop-MNPs killed cancer cells in a dose-dependent fashion, with 50+6.8% cell killing of D283 cells (for example) with 24 hours of treatment after remote targeting. U138 and H2122 cells were found to be even more susceptible to the killing effect of Etop-MNPs than D283 cells. These findings indicate that the novel Etop-MNPs have a cytotoxic effect, and can be moved relatively rapidly at physiologic distances, using a rotating magnet. While further testing is needed, intrathecal administration of Etop-MNPs holds promise for magnetically-enhanced eradication of cancer cells distributed within CSF pathways, particularly if given early in the course of the disease.